Kejadian Dismenorea Pada Mahasiswi Universitas Pasir Pengaraian Kabupaten Rokan Hulu - Wahyuny, Romy (Jurnal Martenity and Neonatal, 2014)
Dysmenorrhoea or menstrual pain is a symptom and not a disease. Menstrual pain arising from the contraction of the myometrium distrimik that displays one or more symptoms ranging from mild pain to severe pain. In Indonesia Harunrianto (2008) the incidence of dysmenorrhoea by 64.25%, the purpose of research known relationships regular exercise, nutritional status, family history, early menarche at age, duration of menstruation, and menstrual cycles with disminorea events at Sand University student Pangaraian District Rokan Hulu in 2014.This research is a quantitative study with cross sectional research design. Number of samples 220 Sand Pengaraian University student Rokan Hulu. The sampling procedure by means of systematic random sampling, data collection and analysis of data using questionnaires univariate, bivariate chi - square, with a multivariate multiple logistic regression.The results obtained are subjected to as many as 131 people dysmenorrhoea (59.5%), variables related to the incidence of dysmenorrhoea is long menstruation (POR: 4.4: 95% CI: 1.558 to 12.684)), and family history (POR: 3 , 5: 95% CI: 1.792 to 6.925).The conclusion of this study is that there is a relationship between duration of menstruation and dysmenorrhoea family history events.Advice for a student is expected to better anticipate and be aware of the occurrence of anxiety dysmenorrhoea, then try to avoid and eliminate the factors that can affect the pain, such as stress and anxiety that often arise at the time before menstruation.